The Influence of Work Motivation, Technical Training, and Work Environment on Employee Performance through Job Satisfaction in the Mineral Downstreaming Sector: A Case Study of PT. XYZ - Fauzi Arie Priyatno; Susanti Widhiastuti (Masterpiece, 2026)
This study examines the determinants of employee performance within a highly structured and operational work environment by analyzing the roles of work motivation, technical training, and work environment, with job satisfaction as a mediating variable. A quantitative approach was employed using a survey method involving 272 employees of PT Borneo Alumina Indonesia, selected through proportionate stratified random sampling from a population of 852 employees. Data were analyzed using multiple linear regression, complemented by classical assumption tests and Sobel test for mediation analysis. The results indicate that technical training and work environment have a significant positive effect on job satisfaction, while work motivation does not significantly influence job satisfaction. Furthermore, work motivation, technical training, and job satisfaction significantly affect employee performance, whereas the work environment does not have a direct significant effect. Job satisfaction is found to mediate the relationship between technical training and work environment on employee performance, but does not mediate the effect of work motivation on performance. These findings suggest that in a structured work setting, employee performance is more strongly driven by capability and system-related factors rather than motivational aspects.